Massive hemoptysis (M.H.) - Porras, Yamandú (Cirugía del Uruguay, 1972)
The author presents a case of massive hemoptysis which determined a surgical treatment for a double lesion: 1) Retention of an hydatic membrane in the upper left lobe which was treated with an atypical resection. 2) Lower lobe spoiled by bronchiectasis and chronic pneumonitis treated with a lobectomy. Eighteen months later the pacient presented a Jobar pneumonia which was solved by a tracheotomy and by a massive antibiotherapy. The principal point of this work is the reaffirmation of Largheros' concepts in 1942 and the revision of Karlsson's work.